Influence of self-cementing properties on the mechanical behaviour of recycled concrete aggregates under monotonic loading - Wang, Chong; Chazallon, Cyrille; Hornych, Pierre; Braymand, Sandrine (Construction and Building Materials, 2023)
Recently, the use of recycled crushed concrete aggregates (RCA) as a substitution of natural aggregates in pavement base and subbase layers has become more popular. Occasionally, a growth of stiffness and strength in unbound base and subbase layers built with RCA can be observed, which can be considered as self-cementing properties of RCA. In this study, the potential self-cementing properties and the long-term mechanical behaviour of two different RCA (NRCA and ORCA), with significantly different self-cementing properties, were studied by pH value, thermogravimetric analysis (TGA) and monotonic triaxial tests under varying confining pressures (20/40/70 kPa) and varying curing times (1/28/360 days). Results show that the long-term storage can largely reduce the self-cementing properties of RCA (ORCA), while the RCA crushed recently (NRCA) exhibits much stronger self-cementing properties. Besides, the long-term mechanical behaviours are influenced by self-cementing properties and confining pressure as well as curing time, so that the strength and stiffness of RCA specimen, with stronger self-cementing properties (NRCA), increase more under low confining pressure and long curing time. The experimental results also indicate that the long-term mechanical behaviours of NRCA are consistent with cement treated materials, whose ductile stress–strain response gradually turns to stiff brittle behaviour as curing time increases.